Perceived Stress, Alexithymia, and Psychological Health as Predictors of Sedative Abuse - Gilan, Nader Rajabi (Korean J Fam Med, 2015)
BACKGROUND: The harmful effects of sedative medications and substances in conjunction with limited research regarding predictive psychological constructs of drug abuse necessitate further investigation of associated factors. Therefore, the present study aimed to elucidate the roles of perceived stress, alexithymia, and psychological health as predictors of sedative abuse in medical students. METHODS: In this cross-sectional study, 548 students at Kermanshah University of Medical Sciences, Iran, were selected using stratified random sampling. The data were obtained using the Perceived Stress Scale, an alexithymia scale (Farsi version of the Toronto Alexithymia Scale-20), and a General Health Questionnaire to assess psychological health. Data were analyzed using discriminant analyses. RESULTS: The results demonstrated that the user and non-user of sedative substances groups had significantly different predictive variables (except for social function disorder) (P>0.05). Physical complaints, alexithymia, and perceived stress, which had standard coefficients of 0.80, 0.60, and -0.27, respectively, predicted sedative drug use. CONCLUSION: The results of the present study indicate that perceived stress, alexithymia, physical complaints, anxiety, and depression are associated with sedative drug abuse.